2015
DOI: 10.1136/gutjnl-2014-308852
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 25-hydroxyvitamin D and colorectal cancer risk according to tumour immunity status

Abstract: Objective Evidence suggests protective effects of vitamin D and anti-tumour immunity on colorectal cancer risk. Immune cells in tumour microenvironment can convert 25-hydroxyvitamin D [25(OH)D] to bioactive 1α,25-dihydroxyvitamin D3, which influences neoplastic and immune cells as an autocrine and paracrine factor. Thus, we hypothesised that the inverse association between vitamin D and colorectal cancer risk might be stronger for cancers with high-level immune response than those with low-level immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 53 publications
3
82
0
Order By: Relevance
“…In a preclinical SMAD3 knockout model of colitis and colon cancer, Meeker et al (304) showed that a high vitamin D diet decreases NF-B activation in colonic epithelial cells, which is reflected by decreased inflammatory cell infiltrates and reduced expression of proinflammatory cytokines during initiation of carcinogenesis (304). In line with this, a strong inverse association is found between 25(OH)D status and the risk of colorectal cancer with high-level lymphocytic reactions which suggests a role for vitamin D in cancer immunoprevention through modulation of the host-tumor interaction (419). A recent whole genome profiling on cells derived from normal mammary tissue and breast cancer reveals the regulation of a set of immune genes by 1,25(OH) 2 D 3 .…”
Section: D) Effects On Inflammation In Cancermentioning
confidence: 48%
“…In a preclinical SMAD3 knockout model of colitis and colon cancer, Meeker et al (304) showed that a high vitamin D diet decreases NF-B activation in colonic epithelial cells, which is reflected by decreased inflammatory cell infiltrates and reduced expression of proinflammatory cytokines during initiation of carcinogenesis (304). In line with this, a strong inverse association is found between 25(OH)D status and the risk of colorectal cancer with high-level lymphocytic reactions which suggests a role for vitamin D in cancer immunoprevention through modulation of the host-tumor interaction (419). A recent whole genome profiling on cells derived from normal mammary tissue and breast cancer reveals the regulation of a set of immune genes by 1,25(OH) 2 D 3 .…”
Section: D) Effects On Inflammation In Cancermentioning
confidence: 48%
“…Although moderately increased levels of ROS damage DNA and promote mutagenesis in cells, recent evidence indicates that high ROS levels exert an oxidative stress that can restrain tumor progression and metastasis by causing cell senescence or death. [27,28] Several lines of evidence also support a beneficial effect of marine ω-3 PUFAs on cancer survival. In a randomized controlled trial (RCT) of 60 patients, supplementation of marine ω-3 PUFAs restored the decreased ratio of T-helper cells to T-suppressor cells and prolonged the survival of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are, for example, important distinctions between such clinically relevant subgroups, including hormone receptor status in breast cancer, histological subtypes of non-Hodgkin lymphoma and ovarian, lung, and gastric cancers, and disease aggressiveness in prostate cancer. Interestingly, 1 recent study found that a higher vitamin D status was more beneficial for colorectal tumors having greater lymphocytic infiltration (138), supporting the view expressed in a recent commentary that substantially greater attention is needed with respect to organ site-specific biological mechanisms (139). The current literature also suggests that there may be other important factors that interact with vitamin D status, such as menopausal status in breast cancer (17), sex in colorectal cancer (140), and circulating vitamin D binding protein in prostate cancer (141).…”
Section: Current Expert Recommendations Versus Population Trendsmentioning
confidence: 99%